2005
DOI: 10.2105/ajph.2003.033563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Intensive Street-Level Police Intervention on Syringe Exchange Program Use in Philadelphia, Pa

Abstract: Repeated measurements and mixed-effects models were used to analyze the effects of an intensive long-term street-level police intervention on syringe exchange program use. Utilization data for 9 months before and after the beginning of the intervention were analyzed. Use fell across all categories and time periods studied, with significant declines in use among total participants, male participants, and Black participants. Declines in use among Black and male participants were much more pronounced than decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 26 publications
4
99
1
Order By: Relevance
“…[31][32][33][34][35][36][37][38][39][40][41] Notably, however, some past research suggests that SEPs are able to maintain the volume of syringes they distribute during police drug crackdowns, though the number of injectors going to the SEPs declines. 82,83 Our findings suggest that sustaining the volume of syringes flowing into communities when drug-related enforcement activities intensify is not enough; drug-related arrests appear to hinder injectors' ability to actually use these syringes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37][38][39][40][41] Notably, however, some past research suggests that SEPs are able to maintain the volume of syringes they distribute during police drug crackdowns, though the number of injectors going to the SEPs declines. 82,83 Our findings suggest that sustaining the volume of syringes flowing into communities when drug-related enforcement activities intensify is not enough; drug-related arrests appear to hinder injectors' ability to actually use these syringes.…”
Section: Discussionmentioning
confidence: 99%
“…Local drug-related law enforcement activities targeting drug users impede injectors' efforts both to go to SEPs, and to inject safely. [31][32][33][34][35][36][37][38][39][40][41] The relationship between spatial access to syringes and injecting with an unsterile syringe may be attenuated in heavily policed settings.…”
Section: Seps and The Risk Environment: A Conceptual Modelmentioning
confidence: 99%
“…22 Police surveillance of the service points and confiscation of legally obtained syringes in or around these programs may directly interfere in their functioning and reduce their public health impact. 22,34,35 In aggregate, the real and perceived barriers to safer practices and service access help explain the observed associations between report of syringe confiscation and risk behavior among IDUs. 23,24,29,36 Expanding on the findings from a broader initiative to understand the risk environment of FSW-IDUs along Mexico's Northern Border, 16,18 this analysis focuses on identifying behavioral and health status correlates of syringe confiscation.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of 89 metropolitan areas in the United States, Friedman and colleagues [18] showed that higher levels of legal repressiveness (including number of arrests for heroin and cocaine possession) were associated positively with HIV prevalence among IDUs. In Philadelphia, intensified policing activity was associated with a significant reduction in syringe exchange program utilization [19]. At the individual level, a study of 424 IDUs in San Francisco found that those who feared arrest for drug paraphernalia possession were twice as likely to report syringe sharing than IDUs who did not share this concern; however, previous arrest was not associated independently with syringe sharing [20].…”
Section: Introductionmentioning
confidence: 99%